Current Understanding of Natural Antibodies and Exploring the Possibilities of Modulation Using Veterinary Models. A Review - Reyneveld, G. IJsbrand; Savelkoul, Huub F. J.; Parmentier, Henk K. (Frontiers in Immunology, 2020)
Natural antibodies (NAb) are defined as germline encoded immunoglobulins found in individuals without (known) prior antigenic experience. NAb bind exogenous (e.g., bacterial) and self-components and have been found in every vertebrate species tested. NAb likely act as a first-line immune defense against infections. A large part of NAb, so called natural autoantibodies (NAAb) bind to and clear (self) neo-epitopes, apoptotic, and necrotic cells. Such self-binding antibodies cannot, however, be considered as pathogenic autoantibodies in the classical sense. IgM and IgG NAb and NAAb and their implications in health and disease are relatively well-described in humans and mice. NAb are present in veterinary (and wildlife) species, but their relation with diseases and disorders in veterinary species are much less known. Also, there is little known of IgA NAb. IgA is the most abundant immunoglobulin with essential pro-inflammatory and homeostatic properties urging for more research on the importance of IgA NAb. Since NAb in humans were indicated to fulfill important functions in health and disease, their role in health of veterinary species should be investigated more often. Furthermore, it is unknown whether levels of NAb-isotypes and/or idiotypes can and should be modulated. Veterinary species as models of choice fill in a niche between mice and (non-human) primates, and the study of NAb in veterinary species may provide valuable new insights that will likely improve health management. Below, examples of the involvement of NAb in several diseases in mostly humans are shown. Possibilities of intravenous immunoglobulin administration, targeted immunotherapy, immunization, diet, and genetic modulation are discussed, all of which could be well-studied using animal models. Arguments are given why veterinary immunology should obtain inspiration from human studies and why human immunology would benefit from veterinary models. Within the One Health concept, findings from veterinary (and wildlife) studies can be related to human studies and vice versa so that both fields will mutually benefit. This will lead to a better understanding of NAb: their origin, activation mechanisms, and their implications in health and disease, and will lead to novel health management strategies for both human and veterinary species.